Awareness and acceptance of Cochlear Implant (CI) in Hearing Impaired (HI) Adolescents and Adult students - Haripriya, C.H; Anirban, Dasgupta; kumardr, Ankur; Singh, Rakesh; Nitesh, Kumar (Journal of Medical Biomedical and Applied Sciences, 2018)
See the paper